Fine Structures of 8-G-1-(p-YC6H4C ≡ CSe)C10H6 (G = H, Cl, and Br) in Crystals and Solutions: Ethynyl Influence and Y- and G-Dependences - Satoko Hayashi; Kentaro Yamane; Waro Nakanishi (Bioinorganic Chemistry and Applications)
Fine structures of 8-G-1-(p-YC6H4C ≡ CSe)C10H6 [1 (G = H) and 2 (G = Cl): Y = H (a), OMe (b), Me (c), F (d), Cl (e), CN (f), and NO2 (g)] are determined by the X-ray analysis. Structures of 1, 2, and 3 (G = Br) are called A if each Se–Csp bond is perpendicular to the naphthyl plane, whereas they are B when the bond is placed on the plane. Structures are observed as A for 1a–c bearing Y of nonacceptors, whereas they are B for 1e–g with Y of strong acceptors. The change in the structures of 1e–g versus those of 1a–c is called Y-dependence in 1. The Y-dependence is very specific in 1 relative to 1-(p-YC6H4Se)C10H7 (4) due to the ethynyl group: the Y-dependence in 1 is almost inverse to the case of 4 due to the ethynyl group. We call the specific effect “Ethynyl Influence.” Structures of 2 are observed as B: the A-type structure of 1b changes dramatically to B of 2b by G = Cl at the 8-position, which is called G-dependence. The structures of 2 and 3 are examined in solutions based on the NMR parameters.